Optimization of distributed control discrete systems under the quadratic quality criterion - Nijolė Janušauskaitė (Lietuvos Matematikos Rinkinys)
The quadratic functional minimization problem was analysed. The motion trajectory was assumed to be discrete, the optimal control feedback was obtained.